Desain Prototipe Instrumentation Amplifier untuk Sensor SKU SEN0257 pada Kit Couple Tank - Aditya Gautama Darmoyono; Asrizal Deri Futra; Sumantri R. K; K. Kamarudin; Muhammad Syafei Gozali (Politeknik Negeri Batam, 2022)
Analog sensors are devices used in the process industry. These sensors can be used to measure the pressure, flow, temperature, and level of a fluid in a tank. A sensor is an important part of a feedback control system that is commonly used in the process industry. In this research, an analog sensor was used to measure water pressure on a couple tank kit, which was SKU SEN0257. This pressure was converted to the depth of the water in the tank. A problem occurred when the dimension of the tank was small, then the depth change of water could not be read by a controller that connected to the sensor. Therefore, a prototype of instrumentation amplifier using IC OP027 was designed. This amplifier was used to increase the output voltage from the sensor so that it could be read by controller. The circuit that has been designed, managed to produce voltage around the desirable value 0-5V. Problem that arise from this research is the fluctuation in the amplified voltage value that need further improvement on the circuit design.